Generation and maturation of human iPSC-derived 3D organotypic cardiac microtissues in long-term culture - Ergir Ece; Oliver-De La Cruz Jorge; Fernandes Soraia; Cassani Marco; Niro Francesco; Pereira-Sousa Daniel; Vrbský Jan; Vinarský Vladimír; Rubina Perestrelo Ana; Debellis Doriana; Vadovičová Natália; Uldrijan Stjepan; et al. (NATURE PORTFOLIO, 2025)
Cardiovascular diseases remain the leading cause of death worldwide; hence there is an increasing focus on developing physiologically relevant in vitro cardiovascular tissue models suitable for studying personalized medicine and pre-clinical tests. Despite recent advances, models that reproduce both tissue complexity and maturation are still limited. We have established a scaffold-free protocol to generate multicellular, beating human cardiac microtissues in vitro from hiPSCs-namely human organotypic cardiac microtissues (hOCMTs)-that show some degree of self-organization and can be cultured for long term. This is achieved by the differentiation of hiPSC in 2D monolayer culture towards cardiovascular lineage, followed by further aggregation on low-attachment culture dishes in 3D. The generated hOCMTs contain multiple cell types that physiologically compose the heart and beat without external stimuli for more than 100 days. We have shown that 3D hOCMTs display improved cardiac specification, survival and metabolic maturation as compared to standard monolayer cardiac differentiation. We also confirmed the functionality of hOCMTs by their response to cardioactive drugs in long-term culture. Furthermore, we demonstrated that they could be used to study chemotherapy-induced cardiotoxicity. Due to showing a tendency for self-organization, cellular heterogeneity, and functionality in our 3D microtissues over extended culture time, we could also confirm these constructs as human cardiac organoids (hCOs). This study could help to develop more physiologically-relevant cardiac tissue models, and represent a powerful platform for future translational research in cardiovascular biology.